2022
DOI: 10.3390/biomedicines10102585
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles in Thyroid Physiology and Diseases: Implications for Diagnosis and Treatment

Abstract: Extracellular vesicles are spherical subcellular structures delimited by a lipid bilayer and released by most cells in the human body. They are loaded with a myriad of molecules (i.e., nucleic acids and proteins) depending on their cell of origin and provide the ability to transmit a message to surrounding or distant target cells. In several organs, including the thyroid, abundant recent literature reports that extracellular vesicles are responsible for intercellular communication in physiological and patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 110 publications
(139 reference statements)
0
2
0
1
Order By: Relevance
“…Patients with thyroid cancer are mainly diagnosed with PTC and usually respond to conventional therapies. Among PTC, however, a subgroup of patients develops an advanced disease and resistance to standard treatment: tumor cells acquiring invasive capabilities leading to metastasis formation [21]. Recently, novel therapeutic approaches have been proposed [22], but their success is limited since the mechanisms underlying the development of this aggressive subtype of PTC are not yet well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with thyroid cancer are mainly diagnosed with PTC and usually respond to conventional therapies. Among PTC, however, a subgroup of patients develops an advanced disease and resistance to standard treatment: tumor cells acquiring invasive capabilities leading to metastasis formation [21]. Recently, novel therapeutic approaches have been proposed [22], but their success is limited since the mechanisms underlying the development of this aggressive subtype of PTC are not yet well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in the thyroid cancer field, extracellular vesicle function has been investigated by treating cells with extracellular vesicles isolated from the plasma or serum of patients and from conditioned culture media [21]. Tumorigenic progression was only correlated with the presence of specific extracellular vesicle components (proteins, miRNAs, lncRNAs or circRNAs); however, no specific evidence indicates that progression was really due to the identified molecular cargo.…”
Section: Discussionmentioning
confidence: 99%
“…13 Urinary exosomes also hold promise in the diagnosis of thyroid diseases, including malignancies. [17][18][19] Exosomes secreted by thyroid cancer cells have been shown to be important for tumor progression, angiogenesis, and metastasis. 17 In the current study, no significant differences were observed in levels of urine exosome in patients without recurrence, regardless of the intervals from thyroidectomy to trail enrollment; thus, because no recurrences were detected in the study the detected exosomes were not released from tumor, but from other cell sources.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] A number of studies have indicated that exosomes hold promise in the diagnosis and management of thyroid diseases, including malignancy. [17][18][19] Our previous study found that urine exosomal thyroglobulin level revealed statistically significant higher in patients with thyroid cancer (stage T3), or with lymph node metastasis. 20 In another pilot study that included 21 patients with thyroid cancer, preoperative urine exosomal tissue inhibitors of metalloproteinases (TIMP) and angiopoietin-1 levels were associated with lymph node metastasis.…”
Section: Introductionmentioning
confidence: 97%
“…Estas dan lugar al DTC (papilar y folicular) y al cáncer anaplásico de tiroides. El segundo tipo de células son las parafoliculares o C, las cuales producen la hormona calcitonina y dan origen al DTC medula (Delcorte O et al, 2022& Sakulpisuti C. et al 2022 En 2022, la European Thyroiud Journal postula que existen dos tipos principales de DTC: papilar y folicular. El cáncer de tiroides papilar es el tipo más común de DTC y representa el 80-90 % de todos los cánceres de tiroides.…”
Section: Introductionunclassified